Dialektika Budaya Dan Kesehatan Dalam Menanggulangi Masalah Stunting Di Desa Sengkerang Lombok Tengah - Aminah, Siti; Suhastini, Novia (Prodi Sosiologi Universitas Mataram, 2024)
Indonesia has a quite serious nutrition problem, marked by a high number of cases of malnutrition, also known as Malnutrition. This malnutrition is a consequence that arises from nutritional status. Indonesia's stunting rate over five years shows an average figure of 36.4% from 2005 to 2017, which is why Indonesia is still categorized as lagging behind. Meanwhile, data from the end of 2022 to the beginning of 2023 shows that the stunting rate in Sengkerang Village is 7.92%. Out of a total of 774 measured toddlers, 74 are experiencing stunting issues. Therefore, this research focuses on discussing the factors influencing the stunting rate in Sengkerang Village and the dialectic of culture and health in addressing health issues in Sengkerang Village. The aim of this research is to identify the factors affecting the stunting rate in Sengkerang Village and to describe how the dialectic of culture and health addresses the stunting problem in Sengkerang Village, Central Lombok. This study uses qualitative research methods with a phenomenological approach. The research results show that the factors causing stunting are as follows: cultural and traditional factors of the community that influence stunting rates, social and economic factors of the family, health and environmental cleanliness factors, the parenting patterns of the current village community towards children, and government policies and interventions. Therefore, a dialectic of culture and health is needed to address the following health issues: 1) Understanding local culture, 2) Collaboration with local figures, 3) Use of media and cultural communication, and 4) Multidisciplinary approach.